The Hidden Forms of Violence in the Lives of Professional Women in Tagamoa, New Cairo - ElHariry, Nouran (AUC Knowledge Fountain, 2024)
The desire to craft new lifestyles is the main drive for the relocation to New Cairo among Egypt’s upper middle classes. This research is focusing on the upper middle class--people who still rely on their incomes from working to maintain their status—as opposed to the elite upper class, who rely on incomes from property, investments, inheritance, and other forms of intergenerational wealth. These communities were enmeshed in high degrees of domestic violence. The power-relations reconfigured in the domestic sphere, with increasing numbers of upper middle class women embarking on professional careers while navigating households and family relations, have opened the doors to new power dynamics that were not previously experienced in this society. There are multiple factors behind the neoliberal economic contribution of those women. The pressures of sustaining certain lifestyles, as well as women’s high levels of education in upper-middle class Egypt, spawned new home cultures, which in turn spawned a specific version of men at that socioeconomic level. This entanglement has resulted in female abuse despite high levels of education and economic independence for women, which, according to my fieldwork, has been linked to a cultural platform of violence against women in New Cairo as a reflection of the individualistic insecurities of men.